Impact of Obesity on Breast Cancer in Premenopausal and Postmenopausal Women - Lubna Elganimi,; Khawla Stuka, (AlQalam Journal of Medical and Applied Sciences, 2026)
Breast cancer remains the most prevalent malignancy among women globally and in Libya, where it accounts for about 41% of all female cancers. Obesity, a modifiable risk factor, has shown differential impacts on breast cancer risk and progression depending on menopausal status. This study investigates the prevalence of obesity among breast cancer patients in Libya and explores its associations with menopausal status, disease stage at diagnosis, and hormonal subtypes. A retrospective cross-sectional analysis was conducted on 210 non-metastatic breast cancer patients treated at Tripoli Cancer Center between 2020 and 2022. Data were extracted from medical records and analyzed using SPSS software. BMI classifications followed WHO criteria, and statistical significance was assessed at a 0.05 level. The mean age at diagnosis was 48.7 ± 10.9 years, with 61.4% of patients being premenopausal. A striking 78.1% of patients had elevated BMI, with 43.8% classified as obese. Luminal B was the predominant hormonal subtype (51%), and stage II was the most common stage at diagnosis (52.4%). Higher BMI was associated with more advanced disease stages, although no statistically significant differences were found between BMI and hormonal or menopausal status. Obesity is highly prevalent among Libyan breast cancer patients and appears to correlate with more advanced disease at diagnosis. These findings underscore the need for targeted public health interventions addressing obesity and its role in breast cancer progression.